The Impact of Social Support and Pregnancy on Subjective Well-Being: A Systematic Review - Battulga, Buyantungalag; Benjamin, Marc Reginald; Chen, Hong; Bat-Enkh, Enkhmandakh (Frontiers in Psychology, 2021)
Background: Subjective well-being (SWB) has a protective role in mental health maintenance and is prone to change during short stressful moments, such as pregnancy. Longstanding research suggests that social support (SS) from the partner and family members of pregnant women directly or indirectly acts as a buffer against negative mental outcomes. For happier pregnancies, it is important to understand how SS and pregnancy affect the SWB. Objective: This review aims to examine the extended association of being pregnant and SS on the SWB of pregnant women. Methods: A systematic review was conducted in PubMed, ScienceDirect, and Google Scholar. Articles published in peer-reviewed journals were included regardless of the year and if they had assessed the impact of at least one SWB or SS outcome among healthy pregnant women. The tools of the National Heart, Lung, and Blood Institute were used for quality assessment. Results: Thirty-four studies that assessed the domains of SWB measurements, such as happiness, quality of life (QoL), life satisfaction, positive and negative effects, and well-being, were included and its association with either pregnancy or SS was summarized. Variable results, such as life satisfaction, happiness, and mental component of QoL, were found to be high during pregnancy, but positive emotion and physical components of QoL had decreased. Almost universally, SS during pregnancy was found to have a positive association with all measurements of SWB. Conclusion: This study had found that, despite some arising trends, pregnancy itself does not necessarily have similar impacts on SWB across healthy pregnant women. However, SS had a significant effect on SWB.